Determination of Received Unknown Signal Modulation Type Using Higher Order Statistics or Spectral Correlation Method - Eduard R. Sivolenko (Изд-во НАН РА)
Nowadays modulated signals are being used everywhere. So, modulation type recognition becomes more important for communication systems. In this paper we suggest a new method to discriminate between two modulated signals: amplitude modulated (AM) and frequency modulated (FM). The simulation results are given below. The method is based on higher order statistics. In this paper we use bispectrum and triple autocorrelation function for signal modulation type recognition.
Keywords: Mathematics